Iliotibial Band Tenodesis With a Tenodesis Screw for Augmentation of Anterior Cruciate Ligament Reconstruction - Richard N. Puzzitiello, B.S.; Avinesh Agarwalla, B.S.; Charles A. Bush-Joseph, M.D.; Brian Forsythe, M.D. (Arthroscopy Techniques, 2019)
Anterior cruciate ligament reconstruction with lateral extra-articular tenodesis using a strip of the iliotibial band (ITB) has been shown to increase postoperative stability of the knee. This Technical Note describes a method of ITB tenodesis in which a central slip of the ITB is passed deep to the lateral collateral ligament and then rerouted anteriorly for fixation at a location anterior and proximal to the lateral femoral epicondyle. Five whipstitches are passed through the ITB, and a second distal suture is tied around the distal end. Of the 4 suture tails, 3 are passed through a tenodesis screwdriver, and the screw is placed in the previously reamed bone socket. A closed loop is formed around the tenodesis screw by tying off the suture tails. This technique creates a sling around the lateral collateral ligament, which serves as a checkrein to internal rotation in cases in which increased stability is warranted, such as revision anterior cruciate ligament reconstruction in an athlete.